Parental health behaviour predictors of childhood and adolescent dietary trajectories. Issue 10 (21st March 2018) - Gasser, Constantine E; Mensah, Fiona K; Clifford, Susan A; Kerr, Jessica A; Wake, Melissa
Abstract: Objective: To determine which parental health behaviours early in childhood most strongly predict whole-of-childhood dietary trajectories. Design: Population-based Longitudinal Study of Australian Children (LSAC, waves 1–6; 2004–2014). Exposures were parents' fruit/vegetable consumption, alcohol, smoking and physical activity at child age 0–1 years (B Cohort) or 4–5 years (K Cohort). Outcomes, from repeated biennial short diet diaries, were group-based trajectories of (i) dietary scores and empirically derived patterns of (ii) healthful and (iii) unhealthful foods consumed, spanning ages 2–3 to 10–11 years (B Cohort) and 4–5 to 14–15 years (K Cohort). We investigated associations of baseline parental health behaviours with child dietary trajectories using multinomial logistic regression. Setting: Australian homes. Subjects: Of children, 4443 (87·0 %) from the B Cohort and 4620 (92·7 %) from the K Cohort were included in all trajectories. Multivariable analyses included 2719 to 2905 children and both parents. Results: Children whose primary caregiver reported the lowest fruit/vegetable consumption had markedly higher odds of belonging to the least healthy score and pattern trajectories (K Cohort: OR=8·7, 95 % CI 5·0, 15·1 and OR=8·4, 95 % CI 4·8, 14·7, respectively); associations were weaker (K Cohort: OR=2·3, 95 % CI 1·0, 5·2) for the unhealthiest pattern trajectory. Secondary caregiver fruit/vegetable associations were smaller and inconsistent. Parental alcohol, smoking and physical activity were not predictive in multivariable analyses. Results were largely replicated for the B Cohort. Conclusions: Low primary caregiver fruit/vegetable consumption increased nearly ninefold the odds of children being in the lowest intake of healthy, but only weakly predicted unhealthy, food trajectories. Healthy and unhealthy food intake may have different determinants.